Inflamma-MicroRNAs in Alzheimer’s Disease: From Disease Pathogenesis to Therapeutic Potentials - Liang, Yuanyuan; Wang, Lin (Frontiers in Cellular Neuroscience, 2021)
Alzheimer's disease (AD) is the most common cause of senile dementia. Although AD research has made important breakthroughs, the pathogenesis of this disease remains unclear, and specific AD diagnostic biomarkers and therapeutic strategies are still lacking. Recent studies have demonstrated that neuroinflammation is involved in AD pathogenesis and is closely related to other health effects. MicroRNAs (miRNAs) are a class of endogenous short sequence non-coding RNAs that indirectly inhibit translation or directly degrade mRNA by specifically binding to its 3’ untranslated region (UTR). A growing body of evidence has demonstrated the specific spatiotemporal expression of miRNA in immune cells, suggesting that miRNA plays an important role in regulating inflammatory responses. Additionally, miRNAs can play two opposite roles, thus activating and inhibiting inflammatory pathways. Therefore, further studies on these inflamma-miRNAs may shed light on the pathological mechanisms of AD. The differential expression of inflamma-miRNAs in the peripheral circulation may respond to AD progression, similar to inflammation, and therefore may become potential diagnostic biomarkers for AD. Moreover, inflamma-miRNAs could also be promising therapeutic targets for AD treatment. This review provides insights into the role of inflamma-miRNAs in AD, as well as an overview of general inflamma-miRNA biology, their implications in pathophysiology, and their potential roles as biomarkers and therapeutic targets.